Performance of maize (Zea mays) varieties in different cropping geometry with greengram (Vigna radiata) - BAISHYA, L K; KAWIKHONLIU, Z; LOTHA, MERYANI M; RAJKHOWA, D J (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted at the ICAR Nagaland Centre during rainy (kharif) season of 2018–2019 and 2019–2020 to check the most suitable maize (Zea mays L.) variety and cropping geometry for maize + greengram (Vigna radiata L.) intercropping system. The results revealed that among the varieties of maize, VHM-45 recorded highest grain yield (4.92 t/ha) and stover yield (14.76 t/ha). Whereas, in intercropping system 1:1 (maize + greengram) recorded highest grain yield (5.16 t/ha) and stover yield (17.06 t/ha). The highest grain yield (1.27 t/ha) and stover yield (2.64 t/ha) of greengram was recorded in sole crop. Maize equivalent yield (MEY) was highest in VHM-45 intercropped with greengram (8.73 t/ha). Whereas, in crop geometry, maize + greengram (1:1) intercropping system recorded the highest MEY (9.16 t/ha). The soil nutrient status after harvest showed an increase in available N, P2O5 and K2O kg/ha in sole or higher density in greengram as compared to others. The competition functions like land equivalent ratio (LER) and aggressivity (A) in maize + greengram prominently indicated benefits of the intercropping system. Similarly, highest profitability and energy efficiency was recorded in VHM-45 among the maize varieties and among the cropping geometry; additive series (maize + greengram 1:1) recorded the highest profitability and energy profitability respectively.